PENERAPAN PEMBANGKIT LISTRIK TENAGA SURYA FOTOVOLTAIK UNTUK MENGURANGI OVER LOAD GARDU DISTRIBUSI KOMPLEK KAWASAN BALAI KOTA YOGYAKARTA - Dulhadi; Utama, Budi (KURVATEK, 2022)
The Yogyakarta City Hall complex area has a PLN electricity supply with a capacity of 875 KVA, a current of 3.977 kA, while the maximum load current absorption is 3.389 kA, so that the percentage of load current to the capacity of distribution substations reaches a maximum limit of 85.09%, assuming a load growth of 1% per year. It is feared that there will be a power outage. So additional power is needed to help overcome the collapse. Potential sources of electricity apart from PLN is new renewable energy photovoltaic solar power. To overcome these problems, PLTS On Grid planning is first carried out. The results of the planning with an area of 1400 m2 produces a power of 204 kWp consisting of 648 solar panels with an arrangement of 18 series and 12 parallel pairs. The AC output voltage and current in the R, S and T phases are 228.63 Volts, 108.2 Ampere, respectively. The contribution of PLTS On Grid in the form of AC power of 24.74 KVA provides additional power of 2.8272% of the capacity of the distribution substation. This addition can save operational costs of IDR 9,826,300 per month. Keywords: Collapse, On Grid PLTS Planning, Savings